VD_FINDINFO Plainte / 2012 / 46 vom 30. November 2012 - VD Tribunal cantonal (2012)
LIQUIDATION SOMMAIRE DE LA FAILLITE, COMMUNAUTÉ HÉRÉDITAIRE, OPC | 652 CC, 14 LDFR, 36 LDFR, 18 al. 1 LP, 231 LP, 256 LP, 1 al. 1 OPC, 16 OPC, 8 al. 1 OPC, 1 al. 1 ORFI, 1 al. 2 ORFI